Crossing borders, pushing margins: Being Italian (im)migrants in the UK and Its Implications - Guzzo, Siria (Margins/Marges/Margini, 2024)
Until recently, relatively little explicit attention has been paid to the Italian migration to the UK, which has received less popularity in the years compared to more well-known waves of migration towards other countries, such as the US, Australia, and South America, for instance. Moreover, not much consideration has been given to a comparison among old and new waves of migration from Italy to the UK and the role paid by more recent events, such as Brexit and the pandemic. Mobility in contemporary history presents fascinating elements which deserve to be explored. Hall (2006) claims that the way we project ourselves into our cultural identities has become increasingly problematic and pulls in multiple directions, consciously shifting from one identity to another, becoming multiple people in multiple places, sometimes performing overlapping identities (Byrd Clark 2007; 2009) according to the context and social interactions with different interlocutors (Guzzo 2010). This therefore leads to a line of questioning into the complexities of self and other identification and a sense of belonging as members of a heritage community in the UK. In this paper, we will specifically discuss how post-Second World War and post-2008 Italian migrants in the UK challenge the margins of their identity(ies) through a re-conceptualisation of the term immigrant. Our analysis begins with the presentation of preliminary data from the research project Migrant food, languages, and identities in the dawn of the post-Brexit and Covid-19 era, funded by the University of Westminster, in London, that investigates how post-2008 migrants who work in Italian food and hospitality businesses use their linguistic repertoires to construct their social identity. From the audio recordings of three dinners with post-2008 Italian migrants in London, we extracted narratives wherein participants explore their migratory trajectories, ideologies, and practices. The comparison of these migrants’ narratives with those of post-war migrants based in Bedford (Guzzo 2014) shows that these two generations of Italian migrants conceptualise their migratory experience in diverse ways, establish different types of networks and construct divergent identities. Our paper concludes with a comparative and contrastive analysis of the discourses of post-2008 and post-war migrants, where we highlight differences and point of connections within the re-framing of the word immigrant, by focusing on the elements and factors that affect the challenge or acceptance of such term.